Role of hepatosteatosis in HBsAg seroconversion in HBeAg‐negative chronic hepatitis B patients. Issue 12 (29th September 2021) - Bacaksız, Ferhat; Gökcan, Hale; Akdoğan, Meral; Gökçe, Dilara Turan; Arı, Derya; Gökbulut, Volkan; Ergün, Yakup; Öztürk, Ömer; Kacar, Sabite
Abstract: Background: In chronic Hepatitis B virus (HBV) infection, certain individual and viral characteristics such as advanced age, presence of hepatic steatosis (HS), normal ALT levels, initially negative HBeAg and HBV DNA, and genotype of the virus are associated with HBsAg seroclearance and seroconversion. Herein, we report the results of our study evaluating the association between hepatosteatosis and HbsAg seroconversion. Methods: The clinical and biochemical data of patients with CHB and hepatosteatosis (HS) (HBsAg seroconversion, n:52, and non‐HbsAg seroconversion, n:352), and the rate of development of HBsAg seroconversion were evaluated. Results: We collected data from 404 patients with HBeAg negative CBH (mean age ± SD: 36.2 ± 11 years; 223 [55.2%] men, 181 [44.8%] women). The mean age at diagnosis of disease was 36.2 ± 11 years. The mean duration of the disease was 10.6 ± 7 years. Seroconversion developed in 52 patients (12.8%) with serum HBsAg positive (mean ± SD: 12.7 ± 5.8). Elderly age and the duration of disease time were significantly associated with seroconversion ( P  < .001). The presence of serum HBsAg seroconversion was significantly associated with hepatosteatosis (OR: 3.06, 95% CI 1.64‐5.71, P  < .01). Serum HBsAg seroconversion was more frequent in patients with mild HS than patients with moderate‐severe HS ( P  = .04). In multivariate regression analysis, the presence of HS was found to be an independent factor predicting the development of HBsAg seroconversion (OR: 2.07 95% GA:1.07‐4.0 P  = .03). Conclusion: The presence of mild HS in HBeAg negative chronic hepatitis B patients contributes to HBsAg seroconversion. Further studies are required to better understand the relationship between steatosis and HBsAg seroconversion.